Sinoatrial node pacemaker cells share dominant biological properties with glutamatergic neurons. Issue 7 (6th February 2021) - Liang, Dandan; Xue, Zhigang; Xue, Jinfeng; Xie, Duanyang; Xiong, Ke; Zhou, Huixing; Zhang, Fulei; Su, Xuling; Wang, Guanghua; Zou, Qicheng; Liu, Yi; Yang, Jian; et al.
Abstract: Activation of the heart normally begins in the sinoatrial node (SAN). Electrical impulses spontaneously released by SAN pacemaker cells (SANPCs) trigger the contraction of the heart. However, the cellular nature of SANPCs remains controversial. Here, we report that SANPCs exhibit glutamatergic neuron-like properties. By comparing the single-cell transcriptome of SANPCs with that of cells from primary visual cortex in mouse, we found that SANPCs co-clustered with cortical neurons. Tissue and cellular imaging confirmed that SANPCs contained key elements of glutamatergic neurotransmitter system, expressing genes encoding glutamate synthesis pathway ( Gls ), ionotropic and metabotropic glutamate receptors ( Grina, Gria3, Grm1 and Grm5 ), and glutamate transporters ( Slc17a7 ). SANPCs highly expressed cell markers of glutamatergic neurons ( Snap25 and Slc17a7 ), whereas Gad1, a marker of GABAergic neurons, was negative. Functional studies revealed that inhibition of glutamate receptors or transporters reduced spontaneous pacing frequency of isolated SAN tissues and spontaneous Ca 2+ transients frequency in single SANPC. Collectively, our work suggests that SANPCs share dominant biological properties with glutamatergic neurons, and the glutamatergic neurotransmitter system may act as an intrinsic regulation module of heart rhythm, which provides a potential intervention target for pacemaker cell-associated arrhythmias.